The Impact of Implementing Human Resource Analytics on Human Resource Management Decision Making - Trisanti, Ayu; Sitanggang, Lestari Pratiwi; Manjorang, Nesa Repinalia Br; Simbolon, Oslan Juliana; Sitompul, Pandapotan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2025)
HR Analytics has become a strategic tool in Human Resource Management (HRM), enabling organizations to make data-driven decisions that enhance operational effectiveness and efficiency. This study aims to analyze the impact of HR Analytics implementation on decision-making in HRM, considering both supporting and inhibiting factors of its implementation. The research uses a quantitative approach, surveying HR professionals across various industries. The findings show that the application of HR Analytics significantly contributes to improving decision-making accuracy, particularly in recruitment, performance management, and employee retention. However, challenges such as limited data literacy, technological infrastructure, and resistance to change remain key barriers to the optimal use of HR Analytics. The study provides implications for organizations to invest more in developing HR analytical competencies and fostering a data-driven decision-making culture. These findings align with the hypothesis that HR Analytics has a positive impact on decision-making and that HR analytical competence strengthens this relationship, while resistance to change weakens its effectiveness. Ultimately, organizations can maximize the benefits of HR Analytics by enhancing analytical skills and minimizing resistance to change.